Excimer Laser no tratamento do vitiligo em 123 pacientes: estudo retrospectivo - Antonio, Carlos Roberto (2011)
Introduction: Vitiligo is cosmetically disfiguring and can cause significant psychological morbidity. Most therapies require protracted treatments and can lead to disappointing results. More recently, 308 nm Excimer laser has proven to be effective in treating vitiligo. Objective: To analyze the effectiveness and patient satisfaction of 308 nm Excimer treatment for vitiligo patches in a variety of locations on the body. Methods: Patients with generalized or localized vitiligo (n = 123, 321 lesions), were studied. The patients were treated at a private practice between 2007 and 2010. Two independent examiners analyzed the response to the therapy by comparing clinical and photographic records before and after treatment. Results: More than half (n = 77) of the patients presented repigmentation greater than 60%, 26 presented 40-59%, and 20% had levels less than 39%. Facial lesions responded better to treatment than those in other body parts. Elbows, hands and feet were the less sensitive areas. In general, the patients were satisfied with the treatment. Conclusion: The use of Excimer laser for treating vitiligo was effective and safe, producing satisfactory cosmetic results and improving patients' self esteem.